Survival of Prosthodontic Restorations Luted with Resin-Based versus Composite-Based Cements: Retrospective Cohort Study - Staněk, Ján; Riad, Abanoub; Le, Adam; Bernát, Matěj; Hammal, Milad; Azar, Basel (Materials (Basel, Switzerland), 2022)
The purpose of this study was to evaluate clinical performance, survival, and complications of indirect composite inlays, onlays, and overlays on posterior teeth. Digital records of 282 patients treated between 2014 and 2018 were accessed and analyzed retrospectively. The included patients received 469 composite restorations luted with seven different resin-based types of cement, i.e., Filtek Ultimate Flow, Enamel Plus, Relyx Ultimate, Harvard Premium Flow, Relyx Unicem, Filtek Bulk Fill Flowable, and Filtek Ultimate. The restorations had been clinically and radiographically evaluated annually. The mechanical and clinical complications, e.g., debonding, fracture, and secondary caries, were evaluated and recorded. The examined restorations exhibited a high survival rate (84.9%), and failure was found in only 71 cases. Fracture was the most common cause (n = 36), followed by prosthetic work release (n = 19) and secondary caries (n = 16). There was a statistically significant difference between failure and cement material (Sig. < 0.001); the composite-based cements (87.2%) had a high survival rate compared to the resin-based cement (72.7%). Similarly, the cements with high viscosity (90.2%) had significantly higher survival rates than the low-viscosity cements (78.9%). Moreover, onlays showed higher longevity compared to overlays (Sig. = 0.007), and patients aged under 55 years showed less complications (Sig. = 0.036). Indirect composite restoration was a successful solution to tooth structure loss. The material of the cementation is an important part of the success. Higher survival rate was found in our study when the fixation materials with high viscosity were used, thus suggesting using these materials with indirect restorations. Composite-based cements had significantly higher survival rate than resin-based cements.
Keywords: resin cements; survival rate; cohort studies; onlay; complications; inlay; dental cements; overlay